The Association of Mental Health Problems With Preventive Behavior and Caregivers' Anxiety About COVID-19 in Children With Neurodevelopmental Disorders - Suzuki, Kota; Hiratani, Michio (Frontiers in Psychiatry, 2021)
We examined the association of mental health problems with preventive behavior and caregivers’ anxiety in children with neurodevelopmental disorders (NDD) and their caregivers during the coronavirus disease 2019 (COVID-19) pandemic. Data were obtained from 227 pairs of children with NDD and their caregivers in a clinic in Fukui Prefecture, Japan, from October 1 to December 31, 2020. During this period, the activities of children and caregivers were not strongly restricted by the public system. Caregivers’ anxiety about children’s activities was positively associated with caregivers’ and children’s fears of COVID-19 and children’s depressive symptoms. Children’s preventive behavior was negatively associated with children’s depressive symptoms. These findings suggested that caregivers’ fear of COVID-19 stemmed from worry about the relationship between children’s activity and COVID-19 infection, and children might have reflected caregivers’ expressions of concern. In schools and clinics, practitioners educate children on how to engage in preventive behavior against COVID-19. Our results support the effectiveness of such practices in mitigating mental health problems in children with NDD.